Pemanfaatan Bakteri Probiotik untuk Menekan Infeksi Colletotrichum acutatum dan Meningkatkan Mutu Benih Cabai (Capsicum annuum L.) Selama Penyimpanan - Anna Tefa; Eny Widajati; Muhamad Syukur; Giyanto Giyanto (Savana Cendana, 2016)
This study aimed to obtain probiotic bacteria that are antagonistic bacteria to Colletotrichum acutatum and to improve chilli seeds quality. The purpose of this study was to obtain probiotic bacteria antagonistic to C. acutatum and prevent seed-borne diseases. The layout of the experiment arranged in completely randomized design factorial design with two factors. The first factor is the seed coating that consists of 6 levels i.e control / without coating (c0), coating without bacteria (c1), coating Bacillus sp. (c2), coating Pseudomonas sp. (c3), coating Actinomycetes sp. (c4) and fungicidal coating (c5). The second factor is the storage period is 0, 1, 2, 3, 4 and 5 months. The results showed that three bacteria that are antagonistic to C. acutatum, i.e.Actinomycetes sp. (ATS6) having inhibition percentage of56, 8%, Bacillus sp. (B48) having inhibition percentage 56,7% and Pseudomonas sp. (P12) having inhibition percentage 46,7%. Application of probiotic bacteria increased viability and the health of chilli seed for storage period of 5 months, seen from maximum growth potential 80-84%, germination capacity 76-78,7%, infected seeds in coating of Actinomycetes sp., 2,6% and Bacillus sp., 6,7%.Bacillus sp. contained 91,8 ppm indole acetic acid (IAA) and 103,2 ppm giberelins (GA3), Actinomycetes sp. contained 89,6 ppm IAA and 92,5 ppm giberelin and Pseudomonas sp. contained 68,9 ppm IAA and 69,2 ppm giberelin.